2011
DOI: 10.1007/s00216-011-4932-4
|View full text |Cite
|
Sign up to set email alerts
|

Determination of phenylenediamine isomers in hair dyes by coal cinders micro-column extraction and MEKC

Abstract: A new micellar electrokinetic chromatography (MEKC) method using beta-cyclodextrins (β-CDs) and 1-butyl-3-methylimidazolium hexafluorophosphates (ionic liquids) as additives was successfully developed for determination of para-, meta-, and ortho-phenylenediamines isomers (p-P, m-P, and o-P) in hair dyes. To improve the sensitivity of the MEKC-UV, a simple and cheap flow injection (FI) technique using a micro-column packed with coal cinders (the by-products from combustion in a boiler) as solid-phase extractant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Suitable method was developed. Wu et al (2011) CD also helps in altering the taste and removal of undesirable bitter tastes and odors of food products. Certain food products have a very bad smell but, on addition of CDs during their manufacturing, inclusion complexes are formed between CD and food components thereby improving the smell of the resultant product.…”
Section: Cds In Nutrition Industrymentioning
confidence: 99%
“…Suitable method was developed. Wu et al (2011) CD also helps in altering the taste and removal of undesirable bitter tastes and odors of food products. Certain food products have a very bad smell but, on addition of CDs during their manufacturing, inclusion complexes are formed between CD and food components thereby improving the smell of the resultant product.…”
Section: Cds In Nutrition Industrymentioning
confidence: 99%
“…The coal cinder of 130 -160 mesh size (obtained from the boiler house of Hubei Normal University) was immersed in 3.0 mol/L hydrogen chloride (HCl) and sodium hydroxide (NaOH), each for 24 h, filtered, washed with DDW until it became neutral and dried prior to storage for later use. The results of Brunauer-Emmett-Teller (BET) measurements and the curve of nitrogen desorption (32) showed that the specific surface area of the coal cinder was 50.3 m 2 /g 21 , and the pore size distribution (PSD) curve for the coal cinder was narrow (approximately 2-4 nm).…”
Section: Chemicals and Reagentsmentioning
confidence: 99%
“…Further study is still required to assess their real potential in MEKC. In one, Wu et al developed a new MEKC method using β‐CDs and 1‐butyl‐3‐methylimidazolium hexafluorophosphates (ionic liquids) as additives for the determination of phenylenediamine isomers in hair dyes.…”
Section: Approaches To Improving Resolutionmentioning
confidence: 99%